Students' Perception of AI Tools in Boosting Motivation for English Learning - Suseno Yudho Purnomo; Muhammad Akbar Setyo Derawan; Muhamad Yusuf Irfan; Fahriany (Universitas Islam Negeri Palopo, 2025)
Artificial Intelligence (AI)-based tools such as ChatGPT, Grammarly and Google Translate are being used more in English language learning but studies have focused mostly on their technical effectiveness rather than associated emotions or motivation. This qualitative descriptive study explored how students perceived the effects of AI tools on their motivation, confidence, and engagement in learning English. At UIN Syarif Hidayatullah Jakarta, data were obtained from 36 fifth-semester English Education students. All participants received a questionnaire, and for the structured interview, five students were selected. The analysis was conducted inductively, and thematic responses from the questionnaires were complemented and used to illustrate the derived themes. The vast majority of students, 77.8%, stated that using AI tools helped them understand difficult materials and receive feedback instantly. The same percentage (72.3%) said they felt more comfortable and confident practicing English with AI, and 72.3% felt more actively involved and had more fun. 54.3% of the participants stated that using AI tools motivated them to perform more difficult tasks, while 30.6% said they did not have a problem with this. The accuracy and overuse of AI tools were the main issues identified by the participants. This study demonstrates that AI tools have altered the emotional and engagement aspects of learning English as a Foreign Language (EFL).